European Union Should Actively Stimulate and Harmonise Neonatal Screening Initiatives - J. Gerard Loeber (MDPI AG, 2018)
Neonatal screening programmes have been introduced in almost all European countries. In practice there are large differences, especially in the panel of conditions that are screened for, often without clear reasons. Policy making on a European level is lacking in contrast to the situation in the USA. Professionals have the knowledge to expand the panels but are dependent on policy-makers for the necessary funds. This paper is a call on the EU Commission to take up a role in providing equal access to neonatal screening for all children within the EU.